The use of by-products in sugar-cane, sugar and alcohol productions - de Conti Medina, Cristiane; Brinholi, Oswaldo (Pesquisa Agropecuaria Brasileira, 1998)
In order to study the effect of gypsum, lime and the mixture of lime-gypsum, associated with syrup in the agricultural and industrial production and in the rooting of sugar-cane (Saccharum spp.), var. IAC 58-480, one experiment was carried out in soil "Terra Roxa Estrutura". Sugar-cane was planted in November 1986, and the cane-plant harvesting in September 1988. Three successive harvests were collected. The experiment was set in a randomized block design with seven treatments and four replications .The treatments were: T1 - 1.2 ton/ha of lime; T2 - 0.8 ton/ha of lime + 0.4 ton/ha of gypsum; T3 - 0.6 ton/ha of lime + 0.6 ton/ha of gypsum; T4 - 0.4 ton/ha of lime + 0.8 ton/ha of gypsum; T5 - 1.2 ton/ha of gypsum; T6 - 2.4 ton/ha of gypsum; T7 - control. Syrup was applied at the amount of 45 m3/ha. In September 1990, after the third harvesting, the second application of the treatments was made, the gypsum being applied in amounts four times greater than those of that put into practice at the planting. During harvest, the following parameters were evaluated: number, length and average diameter of the stalks; yield; and probable sugar and theoretical alcohol production per hectare. The results showed that the second application of the treatments recuperated the crop. Greater yields were achieved when the gypsum was associated with lime or syrup.